Bodybuilding Clubs as Creators of Fit Bodies: A Case Study of Women Members of Shiraz Bodybuilding Clubs - maryam sadat delavar; esfandiar ghafari nasab (توسعه اجتماعی, 2022)
Although fatness is a medical issue, it strongly adheres to cultural logic. Nowadays, cultural logic dictates weight loss and sends a lot of people to weight loss and fitness centers. In the meantime, women and their bodies have been judged more. Therefore, the present study has tried to answer the question of why and under what conditions women go to sports clubs and what strategies they adopt. In this regard, the qualitative approach of grounded theory was used. The participants were twelve women who referred to the clubs of Shiraz. Data were collected through semi-structured in-depth interviews. After the presence of the researcher in the research field, based on the data obtained from the field, in-depth interviews were conducted with the individuals and the interviews continued until the theoretical saturation was reached. Data analysis was performed by open, axial and selective triple coding method. Analysis of the findings led to the creation of six axial categories and one core category. Key categories include: fitness as a measure of beauty, important others' expectations, body empowerment, media representation duality, lifestyle priority over medication, and other social endorsements. The core category is: self-regulation and other social validation.